Aspiration and Desperation Traps in Trajectories of Physical and Social Mobility-Immobility: Young Female Migrants in the City. Issue 2 (1st June 2021) - Bal, Ellen; Shewly, Hosna J.; Laila, Runa
Abstract: Over the last two decades, Bangladesh has experienced a dramatic shift in terms of female rural–urban migration, often referred to as the feminization of migration. Drawing on extensive ethnographic research on young female migrants' livelihood experiences in Dhaka and Gazipur, this article makes three contributions to the migration and mobilities literature. First, while migration often constitutes an adequate tool for resolving desperation, it may also cause an aspiration-desperation trap . Secondly, the transformative potential of migration and mobility for changing social relations of class and gender is not always as effective as it is argued. Lastly, by focusing on the temporalities of migrants' circumstances, we argue that migration is a continuous process in which mobility and immobility are deeply entangled.